Moderate and high sport specialization level in ice hockey athletes is associated with symptomatic cam deformity - Nguyen, M.; Bixby, S.; Yen, Y.-M.; Miller, P.; Stracciolini, A. (Sports Health: A Multidisciplinary Approach, 2023)
Background: There is a known association between ice hockey and cam deformity in growing athletes. Similarly, the association between sport specialization and overuse injury in youth athletes has been well established. Limited research exists examining the relationship between cam deformity and sport specialization.